Assessment of sustainability by models and analyses. Issue 1 (2nd January 2016) - Jørgensen, Sven Erik; Nielsen, Søren Nors
ABSTRACT: There has lately been an increased interest in sustainability assessment and models have been developed to assess the sustainability of ecosystems, a natural area for instance a landscape and of a well-defined area that includes not only ecological processes but also socio-economic activities. Our experiences with sustainability assessment projects are still very limited, but from many sides it has been proposed which key variables to include in such an analysis. The use of work energy as a sustainability indicator that includes expressions of natural and socio-economic activities has been proposed and also tested with a reasonable success. The efficiency of the use of work energy in general and the amount of work energy needed to maintain the various subsystem and their capacity of work energy were included in this analyses. It is, however, clear that one indicator is insufficient to assess a sustainability of a very complex system. It has therefore been proposed to supplement the use of work energy as indicator with development of models of the most important cycles for natural and socio-economic systems, namely the cycles of carbon, nitrogen and water. Two ecological factors are in focus when it is discussed what is important to include in a sustainability analysis, namely the services offered by the ecosystems and the biodiversity, which is important for the spectrum of resistances to possible impacts on the systems. It is probably important to include these two ecological factors as direct indicators in the sustainability analysis, although they are both to a certain extent covered by the work energy analysis. Socio-economic indicators are of course also needed but it is beyond the scope of this presentation.The result of use of models for the sustainability assessment of a Danish island, Samsø that is using renewable energy will be presented as an illustrative example. The overall conclusion of the presentation is that modelling is a very useful and powerful tool to assess the sustainability and it can strongly be recommended to use the positive experience gained up to now when sustainability analyses will be increasingly needed in the future. The presented methods lead to an assessment of sustainability, determination of carbon dioxide emission and a carbon balance for a given area. They can therefore be used for instance for areas of 10 × 10 km whereby the spatial distribution can be illustrated and a geo process model be developed.